Mesenchymal Stem Cells Facilitate Fracture Repair in an Alcohol-Induced Impaired Healing Model - Obermeyer, Thomas (2012)
OBJECTIVES: Clinical studies have shown alcohol to be a risk factor for traumatic orthopaedic injuries and for nonunion. Data from animal studies suggest that alcohol exposure inhibits fracture healing. This report presents a novel rodent model of impaired fracture healing caused by repeated alcohol exposure. Using this model, we examined the regenerative effects of an intravenously administered population of isolated and expanded MSCs on fracture healing. METHODS: Bone marrow-derived MSC were isolated from transgenic Green Fluorescent Protein (GFP) C57BL/6 mice and culture expanded using a lineage depletion protocol. Adult wild-type C57BL/6 mice were subjected to a two-week binge alcohol exposure paradigm, (3 days during which they received daily intraperitoneal injections of a 20% alcohol/saline solution followed by a four-day rest period and another 3 consecutive day binge cycle. At completion of the second binge cycle, mice were subjected to a midshaft tibia fracture while intoxicated. Twenty-four hours following fracture, animals were administered an intravenous (IV) transplant of GFP-labeled MSC. Two weeks following fracture, animals were euthanized and injured tibiae were collected and subjected to biomechanical, histologic, and micro-computed tomography analysis. RESULTS: Pre-injury binge alcohol exposure resulted in a significant impairment in biomechanical strength and decrease in callus volume. MSC transplants restored both fracture callus volume (p<0.05) and biomechanical strength (p<0.05) in animals with alcohol-impaired healing. In vivo imaging demonstrated a time-dependent MSC migration to the fracture site. CONCLUSIONS: These data suggest that a two-week binge alcohol exposure significantly impairs fracture healing in a murine tibia fracture model. IV-administered MSC were capable of specifically homing to the fracture site and of normalizing biomechanical, histologic, and microCT parameters of healing in animals exposed to alcohol. Understanding MSC recruitment patterns and functional contributions to fracture repair may lead to their use in patients with impaired fracture healing and nonunion.